A Need to Balance Between Human Behaviour & Artificial Intelligence - Singh, Priyanka (Global journal of Business and Integral Security, 2025)
In the study, the crucial theme is artificial intelligence (AI) and its complex relationship with human behavior. Employing a quantitative research design, the study surveyed 504 employees from various organizations utilizing AI. Data was collected using structured questionnaires focusing on perceptions of AI’s effects. The collected data was analysed using SPSS software, developed by IBM. Through the, a number of statistical tests such as reliability analysis, descriptive statistics, spearman‘s correlation and ordinal regression was applied in order to analyse the dataset. The study thus confirms the hypothesis that the AI integration in the workplace boosts the efficiency and productivity of employees since their responsibilities are rationed and they are given insights and assistance in decision making. However, contrary to expectations, the employment of AI does not eliminate or minimize work stress or pressure. The means that, it did not influence the stress levels because of difficulties in transitioning to such technologies and pressure for high performance while using AI tools. The study also shows that there is negligible impact of AI integration on the personality traits and attitude of the employees which gives paramount evidence that the nature and basic characters of the people do not change due to the implementation of AI technology. On the positive side AI also provides the basis for continuous skill vi enhancement, where employees can acquire new skills as well as fine-tune their existing skills that is essential in a rapidly changing environment for employees‘ growth on the career ladder. Job Suitability influenced by productivity, skills Training and Development, and attitudes towards work has got a stronger impact on job satisfaction. The comprehensive insight can be considered a useful resource for any organization that is attempting to incorporate AI while ensuring a positive company climate. Such outcomes of AI utilization in the organization‘s processes should demonstrate the necessity of organizations adopting a multi-faceted approach that will address both the technical side of implementing AI and also the psychological and emotional states of the employees.